2009
DOI: 10.1016/j.jcrs.2009.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of intrastromal corneal ring segments in keratoconus

Abstract: Five years after ICRS implantation, the UDVA and CDVA were improved in eyes with keratoconus. There was significant postoperative corneal flattening that remained stable over the follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
117
2
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(135 citation statements)
references
References 25 publications
8
117
2
8
Order By: Relevance
“…These results are consistent with those found in the literature, as most of the studies that have been carried out reported a gain of lines in UDVA. 6,7,10,21,27,28 We observed that the most significant increase in the UDVA was found in patients classified as grade plus, where more than 77% gained 1 or more lines of UDVA. Furthermore, in this group of patients we observed the least number of eyes losing 1 or more lines of UDVA (Tables 6 and 7).…”
Section: In This Study We Evaluated the Outcomes Of Icrsmentioning
confidence: 66%
“…These results are consistent with those found in the literature, as most of the studies that have been carried out reported a gain of lines in UDVA. 6,7,10,21,27,28 We observed that the most significant increase in the UDVA was found in patients classified as grade plus, where more than 77% gained 1 or more lines of UDVA. Furthermore, in this group of patients we observed the least number of eyes losing 1 or more lines of UDVA (Tables 6 and 7).…”
Section: In This Study We Evaluated the Outcomes Of Icrsmentioning
confidence: 66%
“…29 Segment implantasyonu sonrası görsel ve topografik stabilleşme 6. ayda gelişmekte ve 6. ay ile 5. yıl arasında bir miktar regresyon görülse de bu anlamlı olmamaktadır. [35][36][37] Ancak KİHS implantasyonu ektazinin progresyonunu durduramadığından, progresyonu devam eden hastalıkta implantasyon ile sağlanan düzelme zamanla azalmaktadır. 44 Seçilen segmentin modeli dışında sonuçları etkileyen diğer önemli faktör hastalığın evresidir.…”
Section: Sonuçlarunclassified
“…In advent of alternative treatments, intrastromal ring implantation have been introduced which improves visual acuity and optical aberrations and also corrects refractive errors and mean keratometric data [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%